MKI67 as a potential diagnostic biomarker in pulmonary hypertension - Zhou, Huiling; Gong, Ke; Yang, Yifeng; Wu, Qin; Wang, Qiuguo; Shen, Yadan; Xie, Li; Gong, Yibo; Liu, Haidan; Liu, Jijia (Frontiers in Pediatrics, 2022)
Background Right heart failure results from advanced pulmonary hypertension (PH) and has a poor prognosis. There are few available treatments for right heart failure. Pulmonary artery remodeling, including changes in pulmonary artery endothelial cells to endothelial-mesenchymal cells, and aberrant fibroblast and pulmonary artery smooth muscle cell (PASMC) proliferation, are characteristics of the pathophysiological process of PH. As a result, the clinical situation requires novel PH diagnostic and treatment targets. Methods Monocrotaline was used to create an animal model of PH, and lung tissue was removed for transcriptome sequencing. The targets with the highest differences were chosen for transfection after possible targets were identified using bioinformatic techniques and confirmed by qPCR to examine their function in hypoxic PASMCs. Results After sequencing 781 differentially expressed mRNAs, we compared them with the GEO dataset and found 43 differentially expressed genes. We chose the top three scores for further study and verification and discovered that MKI67, a crucial element of the cell cycle that regulates PASMC proliferation, had the greatest effect. After suppressing MKI67 in PASMCs, both cell proliferation and migration decreased. Conclusion Several potential targets were chosen for this study, and MKI67 was found to play a regulatory role in cell migration and proliferation. This implies that PH can be diagnosed and treated using MKI67.